Unified Total Synthesis of Diverse Meroterpenoids from Ganoderma Applanatum - Šimek, Michal; Bártová, Kateřina; Issad, Samy; Hájek, Miroslav; Císařová, Ivana; Jahn, Ullrich (Organic letters, 2022)
A unified approach to meroterpenoids applanatumols B, V, W, X, and Y produced by the medicinal fungus Ganoderma applanatum and 2'-epi-spiroapplanatumine O is presented. The key synthetic sequence consists of a tandem anionic ketone allylation/oxy-Cope rearrangement/α-oxygenation furnishing an α-aminoxy ketone and a persistent radical effect-based 5-exo-trig cyclization leading to the trisubstituted cyclopentane core. The relative configuration of applanatumol V has to be revised. Some compounds display significant cytotoxic and antioxidant properties.
Keywords: ketony; cyklizace; Antioxidants; Ganoderma; Ketones; antioxidancia; Cyclization